Learning Stimulation in PAUD Institutions to Optimize Early Childhood Development Of Indonesia and Malaysia - Sulaiman, Alfarobi Ahmad; Usman , Jamiludin; Umam, Khoirul (Kiddo: Jurnal Pendidikan Islam Anak Usia Dini, 2024)
This study aims to describe the differences in early childhood learning stimulation approaches between Indonesia (TK PKK Jalmak, Pamekasan) and Malaysia (Prasekolah Kebangsaan Tanjong Sepat). This type of research is descriptive qualitative. By using descriptive qualitative method, the research involved teachers, principals, and early childhood as subjects. The results showed that learning stimulation in optimising early childhood development in Indonesia, focuses more on active learning and children's creativity, while in Malaysia, the approach focuses more on reading, writing and counting skills. In addition, TK PKK Jalmak emphasises freedom of learning and formative assessment, while Prasekolah Kebangsaan Tanjong Sepat focuses on play.